Disfunção cognitiva pós-operatória em ratos idosos: avaliação do envolvimento do estresse oxidativo cerebral - Back Netto, Martins (2017)
Postoperative cognitive dysfunction (POCD) is a syndrome defined by a drop without cognitive performance assessed by a set of neuropsychological tests before and after a surgical procedure. The etiology of POCD is still unknown but ani-mal studies have suggested that an POCD may be caused by: excessive neuroin-flammation following surgery and failure to resolve the inflammatory process. Associ-ated with this, it is known that oxidative stress as a result of neuroinflammation may be one of the causes of neuronal damage. Objective: to evaluate the possible cere-bral oxidative involvement in POCD in an experimental fracture model in the elderly rats. Methods: Wistar rats submitted to an experimental model of tibial fracture. The results obtained are analyzed from samples of the hippocampus and prefrontal cor-tex 24 hours and 7 days after the procedure. Parameters determined: oxidative dam-age in lipids and proteins; Activities of oxidizing enzymes (superoxide dismutase-SOD and catalase-CAT). Cognitive deficit was assessed 7 days after the procedure by the open field test and the object recognition test. The statistical analyzes were performed using the SPSS® version 20.0 program with significant results for p <0.05, the graphs constructed were not Graphpad Prism® version 6. Results: The lipid damage showed an increase in the hippocampus in the fracture group on the sev-enth postoperative day compared to the control group. Protein damage showed sig-nificantly higher values on the first postoperative day in the fracture group in both the hippocampus and the prefrontal cortex The antioxidant enzymes SOD and CAT showed a significant decrease in their activity in both structures on the first postope-rative day in the fracture group. In the behavioral tests the rats of the control group presented a decrease in the number of crossings, which did not occur with the frac-ture group and the fracture group presented a significant increase in the number of rearings compared to the control group. In the object recognition test, the fracture group presented impairment in long-term memory. Conclusion: It was concluded that in elderly rats submitted to an experimental model of fracture in the tibia, there was an increase in oxidative stress accompanied by long-term memory impairment and habituation of the open field